Interações em [2]rotaxanos: da influência das estações no movimento de rotação em solução à formação de solvatos e similaridade cristalina - Farias, Fellipe Freire Santos de (2024)
Artificial molecular devices often are based on rotaxane molecules due to their intrinsic topological features. A crucial peculiarity of this class of compounds is the ability to carry out molecular movements of one component in relation to the other. These movements are directly related to the interactions present in these molecules. In addition to their potential application as molecular machines, rotaxanes serve as excellent models for studying interactions, both in solution and solid state. Rotaxane molecules exhibit diverse interactions, including intercomponent and intermolecular ones, which can be modulated through structural changes or physicochemical stimuli. The study of interactions still remains little explored, however, it is of great relevance for the understanding and advancing application of rotaxanes in our daily lives, including using them as molecular machines. In this Thesis, structured into three chapters, intercomponent and intermolecular interactions were explored in [2]rotaxanes that contain the tetralactam macrocycle. The objective is to investigate, quantify and properly classify these interactions, which may guide future applications. Chapter 1, scrutinizes the influence of succinamide and fumaramide stations on the pirouetting movement in solution and the complementarity between components in the crystalline solid state. [2]Rotaxanes pairs with similar molecular threads, featuring identical bulky groups while varying only in stations, were employed. The interactions were investigated in solution via NMR experiments with temperature variation techniques and in the crystalline solid state, with data from single-crystal X ray diffraction, using quantum mechanical calculations (DFT). In solution, fumaramide stations based rotaxanes retain more the macrocycle due to the rigidity of the double bond and the interactions established between the components, reducing the pirouetting movement and, consequently, resulting in greater rotational energy barriers. In the crystalline solid state, the succinamide station promotes more interactions due to its greater structural freedom, leading to greater intercomponent complementary fit and increased stabilization energy. Chapter 2 investigates the role of solvent molecules in the crystallization process of rotaxane solvates, employing the supramolecular cluster as a demarcation tool to assess intermolecular interactions. This tool made it possible to propose crystallization mechanisms and, additionally, to determine at which stage of the crystallization process the solvates are formed. Chapter 3 verifies the promotion of molecular and supramolecular crystalline similarity by inserting the tetralactam macrocycle into molecular threads. This heightened similarity arises from similar intercomponent and intermolecular interactions. The IDCG methodology was applied to adequately quantify this similarity. In short, the conclusions of this Thesis provide crucial insights for the development of new materials and technologies based on molecular devices, using interactions as guides.